2010
DOI: 10.5194/aab-53-545-2010
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of type traits in first calving Black and White cows

Abstract: Group of secondary traits such as health, longevity, type and milkability represents some of very important factors for successful milk production. These traits have been given great importance in recent years. In order to realize productive life of dairy cows as long and successful as possible, special attention should be directed to traits of type and body constitution.Objective of the research was to establish heritability coefficients for 14 type traits of first calving Black and White cows, effect of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Heritability error values were in the range from 0.03 to 0.41. Obtained results differ from values reported by Pantelić et al (2010b), because they refer to bull dams which are elite heads of the herd under control. Heritability values of type traits in the studies by numerous authors show great variability depending on the breed, housing system and scoring system.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Heritability error values were in the range from 0.03 to 0.41. Obtained results differ from values reported by Pantelić et al (2010b), because they refer to bull dams which are elite heads of the herd under control. Heritability values of type traits in the studies by numerous authors show great variability depending on the breed, housing system and scoring system.…”
Section: Resultscontrasting
confidence: 86%
“…In the investigation of the heritability of type traits in Black and White first-calving cows, Pantelić et al (2010b), established average values of heritability coefficients in the range from 0.066 (rear legs set) to 0.310 (rump width), whereas the value of the heritability coefficient for dairy form expression was 0.293. Other three traits had similar values of the heritability coefficient (height to withers 0.155, strength and capacity 0.187 and rump position0.178).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to our selection within populations, a controlled introduction of quality genetic material and crossing should be performed in order to achieve faster genetic improvement . The breeding objectives are: Simental breed, the average milk production in standard lactation over 6.000 kg with 4.10% milk fat and 3.60% protein; Holstein Friesian breed in standard lactation over 8.000 kg with 4.00% fat and 3,50% protein (Pantelić et al, 2010). A possible way to improve fattening and slaughter traits in domestic Simmental breed is the systematic crossbreeding with beef cattle breeds, using the effect of diversity breeds, heterosis effect (Simm, 1998) -crosses obtained from crossing domestic cattle of lower production capacity and bulls of beef breeds, French (Charolais, Limousine, Blonde d'Aquitaine), Italian (Chianina, Piemontese), English (Aberdeen Angus, Galloway, Hereford).…”
Section: Genetic Improvement Of Cattlementioning
confidence: 99%
“…Therefore, it seems more appropriate to use other correlated traits for the indirect prediction of longevity. Many authors reported a relationship between longevity and body conformation traits (Vacek et al 2006;Pantelic et al 2010), which achieve moderate values of heritability (Pantelic et al 2010). In addition, type scoring is usually performed during the first lactation; thus, it brings earlier information related to longevity (Novotny et al 2017).…”
mentioning
confidence: 99%